Climate Change Mitigation and Adaptation in National Development Policy Formulation in Indonesia - Maulana, Akhmad Taufan; Andriansyah, Andriansyah; Muksin, Nani Nurani; Satispi, Evi; Samudra, Azhari Aziz; Oktariani, Andina (Syntax Corporation, 2025)
The purpose of this study is (1) to describe the climate change mitigation and adaptation agenda in formulating national development policies. (2) To describe the climate change mitigation and adaptation agenda that is integrated into national development planning. The research method used is qualitative research with literature studies to collect data. The results of the study indicate that: (1) Indonesia has considered the climate change adaptation agenda in formulating national development policies, with the consideration that the adaptation agenda is more suitable and more feasible to be implemented in developing countries. to address the impacts of climate change at the national level.The Indonesian government has taken various measures to address the impacts of climate change. Many public policy documents have been published at the Central Level, through related Ministries/Institutions and Regional Governments.(2) The climate change adaptation agenda has been outlined in the APBN posture in the form of (a) a climate change budget in state revenues, (b) a climate change budget in central government transactions, (c) a climate change budget in distribution to regions and village funds, and (d) a climate change budget in financing